Preferences for different insomnia treatment options in people with schizophrenia and related psychoses: a qualitative study - Waters, Flavie; Chiu, Vivian W.; Janca, Aleksandar; Atkinson, Amanda; Ree, Melissa (Frontiers in Psychology, 2015)
Symptoms of psychosis such as hallucinations and delusions can be intrusive and unwanted and often remain treatment-resistant. Due to recent progress in basic and clinical sciences, novel approaches such as sleep-based interventions are increasingly becoming offered to address the physical and mental health issues of people with severe mental illness. While the primary outcome is to improve sleep, studies have demonstrated that interventions that target symptoms of insomnia can also produce improvements in the severity of psychotic symptoms, quality of life, and functional outcomes. This study presents qualitative data on the attitudes and preferences of people with schizophrenia and schizo-affective disorders to three different types of therapies for insomnia (standard pharmacological, melatonin-based, and cognitive and/or behavior therapy). Interviews included discussions regarding the perceived advantages and limitations of different therapies, enablers to taking up the preferred option, as well as personal strategies that have helped respondents with sleep problems in the past. Results showed that, when given the choice, these individuals prefer psychological and behavioral-type therapy to other sleep interventions because of its potential to support and empower them in taking responsibility for their own recovery. Pharmacological therapies, by contrast, are viewed as useful in managing acute sleep problems, but only as a short-term solution. Overall, the findings underscore the need for patients’ active engagement when making decisions about treatment options.